2022
DOI: 10.1108/imds-05-2021-0336
|View full text |Cite
|
Sign up to set email alerts
|

For free or paid? A comparison of doctors' intention to offer consulting services in eHealth

Abstract: PurposeConsidering both online and offline service scenarios, this study aims to explore the factors affecting doctors' intention to offer consulting services in eHealth and compare the factors between the free- and paid-service doctors. The theory of reasoned action and social exchange theory are integrated to develop the research model that conceptualizes the role of extrinsic motivations, intrinsic motivations, costs, and attitudes in doctors' behavioral intentions.Design/methodology/approachPartial least s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Third, the impact of the number of free- and fee-based consultations on service satisfaction is the opposite. Specifically, the number of fee-based consultations (b = 0.01980) enhances service satisfaction, while the number of free consultations (b = − 0.82730) has the opposite effect, which previous research also identified as a unique phenomenon (Bond et al 2019 ; Chen et al 2022b ). Consultation volume (b = − 0.86980) also negatively influences service satisfaction, which is more substantial than the number of free consultations.…”
Section: Resultsmentioning
confidence: 96%
“…Third, the impact of the number of free- and fee-based consultations on service satisfaction is the opposite. Specifically, the number of fee-based consultations (b = 0.01980) enhances service satisfaction, while the number of free consultations (b = − 0.82730) has the opposite effect, which previous research also identified as a unique phenomenon (Bond et al 2019 ; Chen et al 2022b ). Consultation volume (b = − 0.86980) also negatively influences service satisfaction, which is more substantial than the number of free consultations.…”
Section: Resultsmentioning
confidence: 96%
“…For instance, Bryant et al ( 16 ) found that knowledge-sharing in OHCs can improve physician-patient relationships and health service quality. Similarly, Chen et al ( 20 ) indicated that physicians can benefit from patients and build long-term positive relationships with them when they share knowledge in OHCs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Doctors' knowledge contributions encompass a wealth of medical knowledge that healthcare professionals provide to patients. Knowledge contributions can be paid or free ( 32 ). With paid knowledge contributions, doctors furnish specialized insights, treatment recommendations, and medical expertise for patients who seek personalized guidance by purchasing online consultation services ( 33 ).…”
Section: Literature Reviewmentioning
confidence: 99%